Factors contributing to the disturbance of coagulation and fibrinolysis in dengue virus infection - Yung-Chun Chuang (Journal of the Formosan Medical Association, 2013)
Hemorrhage is one of the hallmarks of dengue hemorrhagic fever. However, the mechanisms that cause hemorrhage are unclear. In this review we focus on the possible factors that may be involved in the disturbance of coagulation and fibrinolysis during dengue virus (DENV) infection. Factors such as autoantibodies and cytokines induced by DENV infection as well as hemostatic molecules expressed on DENV-infected cells, and DENV viral proteins may all contribute to the defect of hemostasis during DENV infection. It is the combination of these viral and host factors that may tilt the balance of coagulation and fibrinolysis toward bleeding in dengue patients.